PAHAM MODERNISASI TERHADAP ASUMSI TEORITIS INDIVIDUALISME DALAM AKUNTANSI SOSIAL - Zulaeha, Sitti; Alimuddin, Alimuddin; Habbe, Abdul Hamid; Mediaty, Mediaty (STIEM BONGAYA, 2020)
This article uses a qualitative method, which aims to understand the phenomenon of research subjects by exploring the meaning of individuals or groups on the problem of modernization understanding of the theoretical assumptions of individualism in social accounting. Using the approach of the Hofstede Dimension Paradigm (1980), which identifies